Studio Production Techniques for High-Quality Audio Recording and Mixing - Fornia, S.I.Kom, M.I.Kom, Fornia, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2023)
Clear sound is essential in creative industries of music and film to create an immersive experience for audiences and listeners. For the reason, sound engineers must know the proper and effective sound recording techniques and the remarkable outcomes that professionals in the creative sector achieve. Some problems that are often encountered in production studios for quality audio recording and mixing are poor room acoustics, damaged or old studio equipment, limited knowledge and skills, external noise in the form of sound interference from outside the studio, not optimal audio processing, problems with mixing because bad mixing can result in unbalanced audio, instruments that are too dominant or too muffled, or other errors in level, panning, and effect settings. For this reason, the author presents the problems in this study, namely: 1). What is a good studio production technique for high-quality recording and mixing? 2). What equipment and software do studio production techniques produce superior recording and mixing? This research is qualitative research that uses descriptive research methods of analysis. Data were collected by observation, literature study and interviews. The data analysis technique used includes four stages, namely data collection, data reduction, data display and conclusions. The purpose of this study is to provide recommendations for studio production techniques to produce quality recording and mixing as well as what tools are needed and provide an understanding of how to use audio recording equipment. The conclusion of this study is that in achieving high-quality recording and mixing, recording and mixing techniques are needed in studio production including choosing high-quality equipment, having careful hearing and using known musical references to compare recording and mixing quality, developing skills and intuition through experience, practice, and experimentation with new techniques, Pay attention to good room setup and appropriate acoustics to create an optimal recording environment, ensuring the introduction of low latency in the equipment and computer systems used to avoid interruptions in recording and mixing.